2021
DOI: 10.1155/2021/8875023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on the Color and Translucency of Monolithic Translucent Y-TZP Ceramics: A Systematic Review and Meta-Analysis of In Vitro Studies

Abstract: Background. Monolithic restorations made of translucent yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) have become popular over the past few decades. However, whether aging affects the color and translucency of monolithic translucent Y-TZP is unclear. Objective. The aim of this systematic review and meta-analysis of in vitro studies was to evaluate the effects of aging on the color and translucency of monolithic translucent Y-TZP ceramics. Materials and Methods. This systematic review/meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 63 publications
4
13
0
1
Order By: Relevance
“…According to our results, acrylic denture teeth exhibited less color stability than composite artificial teeth. This result was in agreement with previous studies reported by Satoh et al (15) Mutlu-Sagesen et al (19) , and Belli et al (21) . This could be related to sorption character of the water by acrylic materials.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to our results, acrylic denture teeth exhibited less color stability than composite artificial teeth. This result was in agreement with previous studies reported by Satoh et al (15) Mutlu-Sagesen et al (19) , and Belli et al (21) . This could be related to sorption character of the water by acrylic materials.…”
Section: Discussionsupporting
confidence: 94%
“…Evaluation of color changes can be performed by visual or instrumental methods. Spectrophotometers are used in preference to visual evaluation as this instrumental assessment remove the subjective reading of visual color comparison (15) . Characterization of color changes was performed by the Commission Internationale d' Eclairage L*a*b* color space (CIE L*a*b*).…”
Section: Discussionmentioning
confidence: 99%
“…1>E>3.7 was the difference, which is regarded clinically acceptable. Our findings matched those of (hang-yuan Zhang et al, 2021, who investigated the effect of aging on the color and translucency of monolithic zirconia and determined that color change after aging was within the clinically acceptable range [40].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, EDS revealed that the subtractively manufactured zirconia (LAVA Plus, 3M Oral Care) had a lower Al 2 O 3 content than the additively manufactured 3Y-TZPs (LithaCon 3Y 230, Lithoz; 3D Mix zirconia, 3DCeram Sinto), which is in line with their overall composition. LAVA Plus (3M Oral Care) is categorized as a highly translucent 3Y-TZP (0.05 wt% Al 2 O 3 ) that contains less Al 2 O 3 than a conventional 3Y-TZP (0.25 wt% Al 2 O 3 ) [32].…”
Section: Discussionmentioning
confidence: 99%